Creating the fermion mass hierarchies with multiple Higgs bosons - Bauer, Martin; Carena, Marcela; Gemmler, Katrin M. (Arxiv, 2016)
After the Higgs boson discovery, it is established that the Higgs mechanism explains electroweak symmetry breaking and generates the masses of all particles in the Standard Model, with the possible exception of neutrino masses. The hierarchies among fermion masses and mixing angles remain however unexplained. We propose a new class of two Higgs doublet models in which a flavor symmetry broken at the electroweak scale addresses this problem. The models are strongly constrained by electroweak precision tests and the fact that they produce modifications to Higgs couplings and flavor changing neutral currents; they are also constrained by collider searches for extra scalar bosons. The surviving models are very predictive, implying unavoidable new physics signals at the CERN Large Hadron Collider, e.g. extra Higgs Bosons with masses < 700$ GeV.
Gesehen am 10.01.2018